2011
DOI: 10.1017/s0007114511004053
|View full text |Cite|
|
Sign up to set email alerts
|

Do prebiotics reduce the number of fever episodes in healthy children in their first year of life: a randomised controlled trial

Abstract: The objective of the present study was to assess the effect of adding specific prebiotics to standard formula feeding on the number of fever episodes in the first year of life. In the present randomised, double-blind, placebo-controlled trial in seven centres in five West European countries, 830 healthy term infants, without a first-degree family history of allergic disease, of mothers who indicated to give only formula feeding were randomised either to receive a standard non-hydrolysed cows' milk-based formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
2
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 29 publications
1
66
2
4
Order By: Relevance
“…Studies in term infants with a family history of allergic symptoms have shown a reduction of infections and al- lergic symptoms. In a large European study in infants without a family history of allergy, we hardly found a difference in the incidence of infections in relation with the supplementation with pre-biotics [11,26]. Studies in preterm infants found a lower incidence of infections in infants receiving a combination of pre-biotics [19].…”
Section: Pro- End Prebioticscontrasting
confidence: 58%
“…Studies in term infants with a family history of allergic symptoms have shown a reduction of infections and al- lergic symptoms. In a large European study in infants without a family history of allergy, we hardly found a difference in the incidence of infections in relation with the supplementation with pre-biotics [11,26]. Studies in preterm infants found a lower incidence of infections in infants receiving a combination of pre-biotics [19].…”
Section: Pro- End Prebioticscontrasting
confidence: 58%
“…14 In a large randomized, double-blind, placebo-controlled trial performed in 830 healthy term infants in 7 centers in 5 West European countries, there was no effect of adding specific prebiotics to standard formula feeding in reducing the number of fever episodes. 49 On the contrary, other data state that infants fed a scGOS/lcFOS mixture were reported to have fewer episodes of physician-diagnosed overall and upper respiratory tract infections (P < 0.01), fever episodes (P < 0.00001), and fewer antibiotic prescriptions (P < 0.05) during the period of intervention and up to the age of 2 y. 38,50 In an open trial including 342 healthy infants comparing standard infant formula with a GOS/FOS enriched formula given during 6 months, at the age of 12 months the incidence of gastroenteritis was reduced (0.12 C 0.04 vs. 0.29 C 0.05 episodes/child/12 months; p D 0.015), the number of children with more than 3 episodes of gastroenteritis tended to be lower (17/60 vs. 29/65; p D 0.06) and the number of children with multiple antibiotic courses/year was lower (24/60 vs. 43/65; p D 0.004).…”
Section: Prebiotics and Stool Consistencymentioning
confidence: 99%
“…Bruzzese et al 25 reported a lower incidence of gastroenteritis in the supplemented group. On the other hand, the study by van Stuijvenberg et al 26 found a non-significant difference in the number of fever episodes.…”
Section: Respiratory and Gastrointestinal Infectionsmentioning
confidence: 84%